Abandoning Theology for Theory: Stephen D. Moore, Gilles Deleuze, and the Secularization of Biblical Studies - Kuhlin, Joel (Svensk exegetisk årsbok, 2025)
It has been a century since the birth of philosopher Gilles Deleuze (1925-95). At his friend's expense, Michel Foucault once joked, saying that un jour ce siecle sera peut-etre deleuzien: "perhaps one day this century will be known as Deleuzian?" Is there truth to the notion that the present moment expresses something of a "Deleuzian aeon" for the humanities, and what are its ramifications for biblical studies? In this article, a leading voice of theory in exegesis, Stephen D. Moore and The Bible after Deleuze: Affects, Assemblages, Bodies without Organs functions as a screen for issues afflicting "high theory" and theorists of continental philosophy. Through a careful review of Bible after Deleuze and its main contributions, Moore’s study addresses the broad difficulties of combining certain aspects of theory with exegesis in Scandinavia, I argue. Specifically, Bible after Deleuze is interesting in the symptomatic role of theory to replace questions of "theology" in relation to the critical study of the Bible. With this in mind, I ask "What challenges can be found to underlie the task of implementing high theory to a methodologically driven discipline, such as biblical studies?" In the end, Bible after Deleuze is to be applauded for its actualization of contemporary continental philosophy for biblical studies. Acting as a secularizing force in biblical studies however, Bible after Deleuze also diagnoses a tendency of "theory" to replace the historical connection of exegesis and theology.